Consequence modeling of dynamic source terms. Issue 4 (9th January 2016) - James, Michael
Abstract : While several dispersion modeling tools provide modeling tools for static situations, it is challenging to model conditions when there are several variables continually changing. This article discusses several modeling approaches to solve the source term of a release event, including: tracking the concentration of vapor inside of a structure; accounting for heat of solution of a leak of strong acid while deluge is applied; and modeling the output from a scrubber given a dynamic input stream. Upon development of the source term, a method for applying the source term to common dispersion modeling packages is explained. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 392–398, 2016